Spanish in Europe today: social dynamics, linguistic spaces and basis for political action - Loureda Lamas, Óscar (HCIAS working papers on Ibero-America, 2024)
The following pages quantify the Spanish-speaking population of Europe, describe its main features and show its most important dynamics, which are explained by the vitality of migratory flows and by the effects of the teaching of Spanish as a foreign language. A population study of Spanish speakers in Europe is presented, which allows us to approach the social and linguistic reality of Spanish on that continent and to plan policies in terms of culture, education and promotion of the language on an international level.
Gesehen am 23.08.2024